Gabriela Olchowa, System adresatywny języka polskiego i słowackiego na początku XXI wieku. Gaudeamus, Hradec Králové 2018, ss. 240 - BALOWSKI, MIECZYSŁAW (Slavia Occidentalis, 2020)
Gabriela Olchowa, System adresatywny języka polskiego i słowackiego na początku XXI wieku. Gaudeamus, Hradec Králové 2018, ss. 240